The Impact of COVID-19 on US Clinical Trial Activity - Glass, Harold E.; Guy, Andy (Archives of Clinical and Biomedical Research, 2024)
The COVID-19 pandemic has certainly been one of the singular events of the twenty-first century. With the initial impact of COVID-19, clinical trial observers and professionals anticipated major interruptions in the conduct of clinical trial research. Many expected site start-ups to slow appreciably, patient enrolment and treatment to drop significantly, and the search for scarce medical staffing resources to become more daunting. The Open Payments database, a public repository mandated by US law, provides us with a more definitive answer to the question about the impact of COVID-19 on the conduct of US clinical trial activity. While a demanding database to use, the Open Payments data demonstrate that there was surprisingly little disruption in the US clinical trial landscape in 2020-2021. There were few changes in who conducted studies, or where these studies occurred. Most critically, overall US clinical trial activity continued to increase, even when COVID-19 related studies are separated from the total payment numbers. Similarly, clinical trial activity trends among the major therapeutic areas continued much as they had before COVID-19. Areas such as oncology continued to grow, while others, such as cardiovascular, continued to decline. Even previously experienced clinical investigators conducted most of the COVID-19 studies. Open Payments contains only US data for commercially sponsored clinical trials. It may be that the results are different for NIH sponsored studies or sites outside the United States.